Transformation of Eugenol and Safrole into Hydroxychavicol - Budi Arifin; Dumas Flis Tang; Suminar Setiati Achmadi (Indonesian Journal of Chemistry, 2015)
Hydroxychavicol is found in betel leaf at low concentration and is reported to have antibacterial, anti-inflammatory, antioxidant, anticancer, and antimutagenic activities. This study aimed to synthesize hydroxychavicol from eugenol and safrole. Isolation of eugenol from clove oil by alkaline extraction method gave 71% yield, while the isolation of safrole from lawang oil by alkaline extraction method, followed by purification using preparative thin layer chromatography, gave 7% yield. Eugenol demethylation and safrole demethylenation with AlCl3 reagent were successfully produced hydroxychavicol. The yields were 28% and 24%, respectively. Mechanisms of the synthesis are proposed in this article.